Polyploidy in the Conifer Genus Juniperus: An Unexpectedly High Rate - Farhat, Perla; Hidalgo, Oriane; Robert, Thierry; Siljak-Yakovlev, Sonja; Leitch, Ilia J.; Adams, Robert P.; Bou Dagher-Kharrat, Magda (Frontiers in Plant Science, 2019)
Recent research suggests that the frequency of polyploidy may have been underestimated in gymnosperms. While there are few reports of polyploids in the genus Juniperus, data are still missing for most species. In this study, we evaluated the extent of polyploidy in Juniperus by conducting the first comprehensive screen across nearly all of the genus. Genome size data from fresh material, together with chromosome counts, were used to demonstrate that genome sizes estimated from dried material could be used as reliable proxies to uncover the extent of ploidy diversity across the genus. Our analysis showed that 16 Juniperus taxa were polyploid, with 15 tetraploids and one hexaploid being reported. Furthermore, phylogenetic analyses provided the first evidence of possible lineage-specific polyploidizations within the genus. Genome downsizing following polyploidization was moderate, suggesting limited genome restructuring. This study highlights the importance of polyploidy in Juniperus, making it the first conifer genus and only the second genus in gymnosperms where polyploidy is frequent. In this sense, Juniperus represents an interesting model for investigating the genomic and ecological consequences of polyploidy in conifers.